Calificación de un baño maría en el área de control de calidad de un laboratorio farmacéutico Piura-2018 - Olavarria Zevallos, Anthony Jesus (2019)
The objective of the present work of preprofessional practices was to qualify a water bath in the quality control area of a pharmaceutical laboratory Piura-2018, for which the descriptive and observational methodology was used. The work was carried out in three stages: installation, operation and performance. In the installation qualification, the characteristics and physical conditions of the environment in which the equipment operates were verified. On the other hand, in the operation qualification, the preliminary conditions for the operation of the equipment were verified and three heat distribution studies of the isothermal medium without load were carried out, and finally for the qualification of performance, heat distribution studies of the medium were carried out. isotherm with charge, to achieve the achievement of the test temperatures of 60ºC ± 2 and 99ºC ± 2, the temperature controller of the equipment must be set to 58ºC and 96,5ºC respectively. In each of these three stages favorable results were found, which allows us to conclude that the water bath equipment intended for homogeneous heating by thermal convection of the water according to the needs of the user in the quality control area of a national pharmaceutical laboratory is qualified